Implementation of Augmented Reality Booklet Based on Problem Based Learning on Earth and Solar System to Increase Students' Scientific Literacy Skills: Penelitian - Masudatut Toyyibah; Agung Mulyo Setiawan; Firda Awalia Putri; Safwatun Nida (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to improve students' scientific literacy on Earth and Solar System material through the use of Augmented Reality (AR)-based booklets integrated with the Problem-Based Learning (PBL) model. Scientific literacy is an important ability in science education, especially to understand abstract concepts and natural phenomena scientifically. The method used in this research is pre-experimental design with one-group pretest-posttest, involving 32 seventh grade students in one of the public junior high schools in Malang City. The instrument used was a scientific literacy description question based on the 2025 PISA framework, which has been validated by experts and field tested. The results showed a significant increase in the average score of students' scientific literacy after treatment, from the